Using Pollination Deficits to Infer Pollinator Declines: Can Theory Guide Us? - Thomson, James D. (Conservation ecology, 2001)
Authors examining pollinator declines frequently discuss pollination deficits, either as contemporary evidence that declines have occurred or as a possible negative consequence of future declines. Because pollination deficits can be measured in short-term studies, it would be useful if such studies could somehow replace painstaking documentation of insect population trends. I examine the legitimacy of this type of substitution with reference to evolutionary theory and natural plant populations. Operationally, pollination deficits are detected through pollen supplementation experiments. Although simple, these experiments are subject to subtleties of interpretation because of biases and nonlinear responses, which I discuss. Although it has been found that, in 62% of the natural populations studied, fruit or seed sets are at least sometimes limited by insufficient pollen, other research suggests that intact natural systems ought to arrive at an evolutionary equilibrium in which reproduction is limited equally by pollination and by maternal resources. Therefore, chronic severe pollination deficits may indicate that the pollinator service of a plant population has declined from some higher level in the past. However, there is no evidence of widespread declines, and, because of stochastic factors in nature, occasional shortfalls of pollination should be expected even at equilibrium. Although the effects of pollination deficits on plant population dynamics have been little studied, moderate declines in seed production may have relatively little effect on population growth rates because resources not expended on fruits and seeds may be reallocated to vegetative persistence or spread. It is therefore premature to conclude that pollinator declines are having strong effects on natural plant populations, but this mostly reflects a lack of data and is no cause for complacency. Theory must be supplemented by case studies; I give one example and recommendations.